Wacana Model Penafsiran Terbaik: Telaah Kritis Produk Tafsir bi al-Ma’thūr Era Mutaqaddimīn - Mahdi Afandi; Abd. Kholid (QOF, 2023)
In addition to the interpretation of the Qur'an using a reasoning approach (ra'yi), the interpreter also used an interpretive method with riwayah or the so-called interpretation bi al-ma'thūr. This interpretation is considered the best model of interpretation by Ibn Taimiyah and Ibn Kaṡīr and has very high validity and argumentation. Even so high, the results of the interpretation of bi al-ma'thūr must be followed and should not be ignored. This study aims to critically analyze and verify the bi al-ma'thur interpretation model that was born in the mutaqaddimīn era. Focusing on two main interpretation books, namely Jāmi' al-Bayān an Ta'wīl Ȃyi al-Qur'an by Muhammad bin Jarīr al-Ṭabari (d. 310 H.), and Baḥr al-‘Ulūm by Naṣr ibn Muhammad al-Samarqandi (d. 375 H). This research used an analytical descriptive approach and is included in library research because the data source came from library-based literature, it also included verification research, which is a type of research used to review the principles and methods of interpretation that have developed from the perspective of its relevance to the times. The results of this study are that although considered the best, the bi al-ma'ṡur interpretation model in fact has problematic deficiencies from various sides. Among them, there are many weak narrations or even munkar narrations, the narrations have minimal isnads so one cannot distinguish which ones are authentic and which are weak, many contain israiliyat narrations without commenting or selecting narrators, and cite narrations from narrators who are considered negative by scholars. Interpretation of this model is recommended to be avoided for whom do not have knowledge related to riwayah and dirayah.